Utilization of "Stand-By" Extracorporeal Membrane Oxygenation in a High-Risk Parturient With Methamphetamine-Associated Cardiomyopathy Undergoing Dilation and Evacuation: A Case Report. Issue 5 (1st March 2017) - Padilla, Cesar; Hernandez Conte, Antonio; Ramzy, Danny; Lubin, Lorraine; LaBounty, Troy; Chung, Judith H.; Zeng, Ying
Abstract : Parturients may present with evidence of acute heart failure or respiratory distress during the peripartum period. This case report documents utilization of "stand-by" extracorporeal membrane oxygenation (ECMO) for a 40-year-old woman with a history of severe left ventricular dysfunction who presented for elective dilation and evacuation of triplets at 20 weeks' gestation. The patient's medical history was significant for hypertension, diabetes mellitus, methamphetamine use (acute/chronic), and cardiac-respiratory arrest before her previous emergent cesarean delivery. The patient underwent general anesthesia with the placement of peripheral venous and arterial cannulas for "stand-by" ECMO. The patient remained stable throughout the procedure, and "stand-by" ECMO was not initiated; the patient was discharged 5 days' postprocedure. The use of "stand-by" ECMO in the parturient with severe cardiopulmonary dysfunction is still in its infancy. Centers managing populations of both high-risk parturients and nonparturients may consider development of algorithms for implementation and utilization of ECMO.